Thermionic properties of LaB₆-(Ti₀¸₆Zr₀¸₄)B₂ material - Paderno, Yu.B.; Taran, A.A.; Voronovich, D.A.; Paderno, V.N.; Filipov, V.B. (Functional Materials, 2008)
The thermionic emmision peculiarities of filber reinforced boride composite ceramic material LaB₆-(Ti₀¸₆Zr₀¸₄)B₂ produced by directional crystallization of eutectic alloy have been studied. Activation modes, electron work function temperature dependence, poisonin under air leakink have been determined. The obtained data are compared with emission characteristics of (100) LaB₆ single crystal and quasi-binary eutectic materials LaB₆-TiB₂ and LaB₆-ZrB₂.